The Influence of Project-Based Learning Model on Learning Outcomes of Class VIII Students At Private Junior High School Tri Sakti Lubuk Pakam - Januaris Pane; Juliper Nainggolan; Emanuel Zega; Febrika Dwi Lestari (JURNAL PENDIDIKAN MIPA, 2023)
Based on the background, the learning model that is often used in class VIII of Tri Sakti Lubuk Pakam Private Middle School still tend to use conventional learning models or lecture methods and only apply His mathematical formulas, resulting in student responses being less enthusiastic and less active whenever Science-Physics learning takes place. So that, this study aims to determine the effect of the learning model Project Based learning on student learning outcomes in class VIII energy material at Tri Sakti Lubuk Pakam Private Middle School. The method used in this research isLike an experiment with a population of all eighth grade students at Tri Sakti Lubuk Pakam Private Middle School. The sample in this study consisted of 2 classes using the technique Purposive Sampling. The instrument used was a learning achievement test in the form of multiple choice item items of 20 questions. Before being given treatment to the sample, a pre-test was first carried out to find out whether the sample came from a normally distributed and homogeneous population. Then given treatment to both classes, namely by giving a test pretest and obtained an average score of 38.00 for the experimental class with a standard deviation of 16.01 and for the control class 40.00 with a standard deviation of 15.75. For the average score Posttest experimental class 77.40 with a standard deviation of 9.35 and control class 62.60 with a standard deviation of 11.00. Homogeneous value pretest to both classes (1.033 <1.983) Fcount smaller than Ftable and value posttest namely Fcount smaller than Ftable (1.379 <1.983), so it can be said that the value pretest and posttest to both samples is homogeneous. Furthermore, for the difference between the two classes, a one-sided t-test was carried out with a = 0.05 obtained (5.120)> (1.677) tcount bigger than ttable which states that there is a difference between the two classes. To see the magnitude of the influence of the model Project Based Learning on learning outcomes a simple regression test is carried out with the equation . So it can be concluded that there is a significant effect of the treatment of the learning modelProject Based Learning on student learning outcomes in class VIII energy material at Tri Sakti Lubuk Pakam Private Middle School